2010
DOI: 10.1111/j.1467-8268.2010.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Per Capita Growth in Africa Hampered by Poor Governance and Weak Institutions? An Empirical Study on the ECOWAS Countries

Abstract: This paper proposes an empirical study of the links between poor governance, weak institutions and the growth of per capita income in the countries that belong to the Economic Community of West African States (ECOWAS). We estimate a conditional beta-convergence model using panel data. We find that variables such as the rule of law, property rights, the regulatory burden, political violence, and government ineffectiveness hinder growth in these countries. An interesting question is then the following: what can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 43 publications
3
27
0
1
Order By: Relevance
“…However, enrolment rate and education expenditure are classified as flow variables that is they show the flow of resources to human capital formation while years of schooling or school attainment are stock variables that is, they measure the stock of educational human capital (Gyimah-Brempong 2011;Barro 2013). Most endogenous growth empirics used enrolment rate as a measure of human capital (Barro 1997;2001;Dowrick 2002;Diop, Dufrenot, and Sanon 2010). Of all these measures of education, school attainment or years of schooling is most preferred as espoused in the literature as it is a measure of stock of human capital but this is often faced with measurement problems and data availability constraints (Easterly and Rebelo 1993;Barro 2013).…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, enrolment rate and education expenditure are classified as flow variables that is they show the flow of resources to human capital formation while years of schooling or school attainment are stock variables that is, they measure the stock of educational human capital (Gyimah-Brempong 2011;Barro 2013). Most endogenous growth empirics used enrolment rate as a measure of human capital (Barro 1997;2001;Dowrick 2002;Diop, Dufrenot, and Sanon 2010). Of all these measures of education, school attainment or years of schooling is most preferred as espoused in the literature as it is a measure of stock of human capital but this is often faced with measurement problems and data availability constraints (Easterly and Rebelo 1993;Barro 2013).…”
Section: Empirical Reviewmentioning
confidence: 99%
“…But, the available expenditure data captures only the federal government expenditure on education and not the consolidated education expenditure as Nigeria operates a three tier government (local, state and federal) where all the tiers have their spending commitment to education and as well the private sector involvement. Besides, Diop, Dufrenot, and Sanon (2010) showed that public expenditures in most ecowas countries would reach the growth objectives if public office holders are made to be more accountable to the public, which has the ability to reducing bribeseeking and rent-seeking behaviours in public investment. This study further reiterated that most of the ecowas countries are faced with diversion of public funds, embezzlements and poor public service delivery.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Regressions show that the largeness of a country and its political stability are positively linked to its growth. Diop, Dufrénot and Sanon (2010) explored the links between governance and institutional characteristics of ECOWAS 5 countries and their growth rate of per capita GDP/income during the period 1995-2004. As we signalled in the introduction, this period is important because in the mid-1990s, Africa's growth recovered from its long-run decline since mid-1970s.…”
Section: Growth In Africa: From the Tragedy To The Odysseymentioning
confidence: 99%
“…Diop et al (2010) attribute the low gross domestic product (GDP) per capita growth of ECOWAS countries to poor governance and weak institutions. They argue that weak institutions and poor governance have made it difficult for citizens of countries within the subregion to attain a higher standard of living.…”
Section: Regional Integration and Industrial Development In Africa: Tmentioning
confidence: 99%